Tissue-specific gene expression in mouse hepatocytes cultured in growth-restricting medium. - Spiegelberg, T (1988)
Culture conditions which maintain hepatocytes in their in vivo state are not known. This hampers the study of liver gene expression and of direct responses of liver genes to hormonal stimulation. We argued that hepatocytes that were unable to divide might retain in vivo characteristics. We therefore plated mouse (BALB/c) hepatocytes on plastic dishes in medium lacking arginine and measured the levels and transcription rates of six tissue-specific mRNAs over a period of days. Alpha-fetoprotein mRNA began to accumulate at about 48 h of culture, and transcription could sometimes be detected after 72 h. The levels and transcription rates of four mRNAs (albumin, alpha-1-antitrypsin, apolipoprotein A1, and major urinary protein [MUP]) fell sharply. The rate of transcription of transferrin mRNA fell less rapidly, and its level remained high, partly due to its longer half-life. The overall pattern of gene expression in the plated cells did not exactly parallel that of either fetal or regenerating liver. The hepatocytes remained responsive to hormonal stimulation. Insulin and dexamethasone each tended to counteract changes in mRNA levels, for example, preventing the accumulation of alpha-fetoprotein mRNA. The effects of insulin were primarily due to changes in transcription rates. Bovine growth hormone and thyroxine elevated the levels of most of the mRNAs. Many of the effects of these hormones, when added singly, could not be ascribed to changes in transcription. The level of MUP mRNA was strongly affected by added hormones. The mRNA level at 5 days was increased by added insulin, dexamethasone, growth hormone, and thyroxine. In the presence of these three hormones, the decay in the transcription rate of the MUP genes was reduced about 10-fold. We conclude that hepatocytes plated under these nongrowing conditions can provide insights into the hormonal responsiveness of tissue-specific genes.